1990
DOI: 10.1002/j.1460-2075.1990.tb07630.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an invertebrate gene encoding cytoplasmic intermediate filament (IF) proteins: implications for the origin and the diversification of IF proteins.

Abstract: The structure of the single gene encoding the cytoplasmic intermediate filament (IF) proteins in non‐neuronal cells of the gastropod Helix aspersa is described. Genomic and cDNA sequences show that the gene is composed of 10 introns and 11 exons, spanning greater than 60 kb of DNA. Alternative RNA processing accounts for two mRNA families which encode two IF proteins differing only in their C‐terminal sequence. The intron/exon organization of the Helix rod domain is identical to that of the vertebrate type III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 70 publications
1
83
0
Order By: Relevance
“…Peptide sequences were deduced by de novo interpretation of their CID mass spectra and used to query genomic databases to assign tentative homologies in sequenced genomes where possible. This effort revealed a number of protein spots with extensive homology to intermediate filament proteins from other mollusks, including Helix (20) and Aplysia (21). During the course of carrying out de novo sequencing of these particular proteins, a number of digest components were discovered from analysis of an LC-ESI-CID-MS experiment that displayed identical mass values for their entire CID sequence ion series (viz.…”
Section: Resultsmentioning
confidence: 99%
“…Peptide sequences were deduced by de novo interpretation of their CID mass spectra and used to query genomic databases to assign tentative homologies in sequenced genomes where possible. This effort revealed a number of protein spots with extensive homology to intermediate filament proteins from other mollusks, including Helix (20) and Aplysia (21). During the course of carrying out de novo sequencing of these particular proteins, a number of digest components were discovered from analysis of an LC-ESI-CID-MS experiment that displayed identical mass values for their entire CID sequence ion series (viz.…”
Section: Resultsmentioning
confidence: 99%
“…genes encoding cytoplasmic IFs suggests that all IF proteins are derived from a lamin-like progenitor (47,48). Early cross-linking experiments showed that the nuclear lamins can form oligomeric structures (42,49).…”
Section: Historical Overview Of Ifs Early Difficulties In the Recognimentioning
confidence: 99%
“…The rod domain is further divided into subdomains 1a, 1b, 2a, and 2b, which are separated by short linker regions referred to as L1, L12, and L2. The cytoplasmic C. elegans IF polypeptides are distinguished by an elongated coil 1b with 42 extra residues which is typical for protostomia and is also a feature shared by all lamins [Weber et al, 1989;Dodemont et al, 1990Dodemont et al, , 1994. Furthermore, the A-and B-type IFs also contain an additional, 110 amino acid-long globular Ig-like fold lamin-homology segment in the tail domain [Weber et al, 1989;Karabinos et al, 2001].…”
Section: Diversity Of Intermediate Filaments In C Elegansmentioning
confidence: 99%